Strategi Efektif dalam Perencanaan Biaya dan Optimalisasi Sumber Pendanaan Satuan Pendidikan Islam - Nayla Eka Syamsiyah; Salsabila Amanda Tsabita; Mardiyah Mardiyah (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to explore effective strategies in cost planning and optimizing funding sources to support the sustainability of Islamic education units. Methodology/approach: The research uses a library research method with a qualitative approach, collecting and analyzing data from various literature sources such as books, journals, and scientific articles related to effective strategies in cost planning and funding optimization for Islamic education units. Results/findings: The study finds that systematic and transparent financial planning, along with the application of digital technology in financial management, can effectively address financial challenges. Transparency and accountability are crucial to increasing stakeholder trust, enabling Islamic education units to operate more effectively and sustainably. Conclutions: By implementing well-structured cost planning strategies and optimizing funding sources, Islamic education units can operate more effectively and sustainably. This research is expected to serve as a reference and make a positive contribution to Islamic educational institutions. Limitations: This study is limited to theoretical analysis based on secondary data without direct field studies or primary data collection. Contribution: This study provides a reference for Islamic education units seeking to implement effective financial strategies, contributing to the field of Islamic education management and finance.